1996
DOI: 10.1007/bf02823875
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of respiratory distress of newborns

Abstract: The present prospective study was conducted to find out the incidence, etiology and outcome of respiratory distress (RD) in newborns. All newborns (n = 4505), delivered at this hospital over a period of 13 months, were observed for respiratory problems. Relevant antenatal, intranatal and neonatal information was noted. Cases were investigated for the cause of respiratory distress and followed up for the outcome. The overall incidence of RD was 6.7%. Preterm babies had the highest incidence (30.0%) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
99
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 12 publications
17
99
0
3
Order By: Relevance
“…3 However in a study done by Kumar A, it was seen that the RDS was found to be the commonest (42.7%) cause of respiratory distress followed by TTNB (17.0%), MAS (10.7%), Sepsis (9.3%) and birth asphyxia (3.3%). 4 This variability in the present study was due to increase no of cesarean deliveries during the study period giving rise to more no of TTNB cases…”
Section: Etiology and Diagnosismentioning
confidence: 63%
“…3 However in a study done by Kumar A, it was seen that the RDS was found to be the commonest (42.7%) cause of respiratory distress followed by TTNB (17.0%), MAS (10.7%), Sepsis (9.3%) and birth asphyxia (3.3%). 4 This variability in the present study was due to increase no of cesarean deliveries during the study period giving rise to more no of TTNB cases…”
Section: Etiology and Diagnosismentioning
confidence: 63%
“…This is lower than findings of Bajad et al in India who reported 32% of all neonatal admissions; but higher than many other previous studies. [6][7][8][9] Abdelrahman et al in Sudan recorded neonatal respiratory distress (NRD) frequency rate of 4.83% among newborn delivered in the hospital but 56.5% among newborn admitted to NICU, Fedakar et al also reported 7% of neonatal admissions in Turkey, Kumar et al in India found overall incidence of 6.7%. [7][8][9] There is therefore, variation in the incidence of respiratory distress at different centres.…”
Section: Discussionmentioning
confidence: 99%
“…RDS, in addition to being a direct reason of mortality, also contributes indirectly by increasing the risk of intraventricular hemorrhage, broncho pulmonary dysplasia and nosocomial infections such as ventilator-associated pneumonia (Kumar and Bhat, 1996). A Comparative study to find out clinical responses to natural and synthetic surfactants had concluded that there are no statistical clinical differences between both surfactants in mortality (Pfister et al, 2007).…”
Section: Introductionmentioning
confidence: 99%